Analyzing trade opening in Ukraine: Effects of a customs union with the EU - Oksana Harbuzyuk; Stefan Lutz (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
This paper analyzes the possible a customs union between and the European Union. The GTAP multi-country simulation model of Purdue University's Center for Global Trade Analysis is applied. The welfare measure evaluated is the change in equivalent variation (EV). As all incomes in the model accrue to a representative household, EV fully assesses possible welfare benefits for Ukraine from a bilateral tariff elimination on trade with the EU. As the model includes Ukraine in the aggregated ,,Former Soviet Union“ region (FSU), EV is estimated for the FSU and then disaggregated on the industry level proportionally to trade shares. The results of our simulations suggest that Ukraine's EV is particularly sensitive to the inclusion of the agricultural sector into a customs union. Due to the highly protected nature of this sector within the EU, Ukraine would be better off if agriculture were excluded from liberalization. If this scenario is assumed, Ukraine's monetary gain would be in the order of 40 million.
Keywords: F02; F15; O19; O52; 330; Ukraine; Trade; Integration; GTAP